Stališča in pričakovanja učiteljev, svetovalnih delavcev in staršev drug do drugega v kontekstu sodelovanja med šolo in domom - Šteh, Barbara (Psihološka obzorja (Ljubljana), 2011)
In this paper we focus on the role of some factors of quality co-operation between the school and the home, particularly focusing on the role of attitudes and expectations of parents, teachers and counselling workers towards each other. The empirical research was carried out in the 2007/08 school year on a representative sample of primary school teachers together with primary and secondary school counsellors and parents of children who attended the third, fifth/sixth and ninth primary school grades in Slovenia. One of the main findings is that teachers, counsellors and parents doubt each other's competences, which is not a sound basis for quality mutual co-operation. Establishment of successful co-operation is based primarily on awareness that both parents and the school share responsibility for the child's development and socialization and that in this shared responsibility they meet as equal interlocutors who confer, through their varied areas of expertise, skills, experiences and sources of power, concerning goals and tasks of mutual co-operation, aimed at supporting and encouraging the child's comprehensive personal development.
Keywords: teachers; učitelji; svetovalni delavci; counselling workers; parents; starši; sodelovanje; cooperation; attitudes; stališča; expectations; pričakovanja; school; šola; sodelovanje med šolo in domom